Prevalence of renal abnormalities in chronic HBV infection: The HARPE study. (3rd March 2014) - Amet, Sabine; Bronowicki, Jean‐Pierre; Thabut, Dominique; Zoulim, Fabien; Bourliere, Marc; Mathurin, Philippe; de Ledinghen, Victor; Benhamou, Yves; Larrey, Dominique G.; Janus, Nicolas; Deray, Gilbert; Launay‐Vacher, Vincent; et al.
Abstract Background & Aims Few data are available on the prevalence of renal abnormalities in chronic hepatitis B virus (HBV)‐infected patients. The multicentric cross‐sectional HARPE study evaluated the prevalence of kidney disease indicators, in chronic HBV surface antigen carriers patients (HBsAg+) with active or inactive infection. Patients and methods Two hundred and sixty‐eight HBsAg+ adult patients, naïve of any oral antihepatitis B virus treatment were prospectively included over 2 years. Data for renal assessment were collected once from patient files. Univariate tests and multiple linear regressions were performed with the SAS software, version 8.02 (SAS, Inc., Cary, NC, USA). Results Among the 260 patients analysed, 58% were men, the mean age was 42 ± 14 years, 59.6% were inactive carriers whereas 47 patients, mostly active, were about to start an antiviral therapy. Prevalence of proteinuria, haematuria, glycosuria, uninfectious leukocyturia was 38.1%, 20.6%, 3.9% and 9% respectively. According to the international definition, a total of 64.6% of patients were found to have kidney disease. Diabetes, hypertension and dyslipidaemia were observed, respectively, in 4.6%, 9.2% and 38.8% patients. There were no significant differences in these results within the three subgroups. Conclusion Renal abnormalities are highly prevalent in our population and pre‐exist before the initiation of any antihepatitis B virus treatment. This emphasizes the need for: (i) a baseline renal evaluation in all HBs antigen‐positive patients; (ii) a regular renal monitoring before and during antihepatitis B virus treatment to diagnose and manage renal impairment and adjust antihepatitis B virus treatment doses to renal function when necessary.